Human papilloma virus profiles in breast cancer in correlation with Vitamin D: papilloma virus in breast cancer and status of vitamin D - Azmi, Hasna; Saif, Imane; Nabil, Kawtar; El Mzibri, Mohammed; Boutayeb, Saber; Lak, Ramin; Ennaji, Moulay Mustapha Ennaji (Cellular and Molecular Biology, 2022)
The major roles of vitamin D in the genesis of breast cancer and as an immunomodulator against acute and chronic infections have been the subject of much research in recent years. A low vitamin D status could decrease the function of blocking the cell multiplication cycle of the cancer process and weaken the immune system. In this context, we were interested in the implication of vitamin D status in women with human papilloma virus (HPV)-induced breast cancer. Our study included 63 women, 53 with breast cancer and 10 healthy women, and we measured the plasma 25(OH)D3 level and looked for the presence of HPV by PCR in our population. 90.6% had low serum 25(OH)D3 levels and HPV was found in 41% of cases. In this regard, the data in the literature are discordant. Vitamin D status could explain the concomitance of the two conditions, breast cancer and HPV; it would be desirable to broaden the sample in order to better define its impact.